On relaxation of the influences of treated sewage effluent on an adjacent seaweed farm in a tidal strait. (July 2019) - Zhang, Xu; Uchiyama, Yusuke; Nakayama, Akihiko
Abstract: An Eulerian passive tracer model coupled with a quadruple-nested 3D circulation model was used to assess the coastal dispersal of treated wastewater effluent from a sewage treatment plant and the associated impacts on an adjacent seaweed farm using three different operational scenarios. When the discharged volume and source effluent fluxes were decreased by ~16.7%, the accumulated effluent in the farm was reduced by ~25.4%. A tracer flux budget analysis revealed the apparent predominance of the transient component that accounts for the nonlinear interactions primarily from tidal currents and eddies. The transient flux promoted the effluent influx to impede effluent accumulation in the farm, whereas the mean flux contributed to the outgoing flux. A source flux reduction caused a remarkable decrease in the transient flux and thus an even greater effluent accumulation reduction. In turn, a modified source density scenario without total effluent volume change did not work as expected. Highlights: A 3D model was used to assess sewage dispersal and its impact on a seaweed farm. Lower source flux results in major decreases dominated by the transient flux. Density adjustment plays a minor role in the effluent dispersal and accumulations.